2014
DOI: 10.3892/or.2014.3269
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage-independent growth of Ewing sarcoma cells under serum-free conditions is not associated with stem-cell like phenotype and function

Abstract: Novel treatment strategies for Ewing sarcoma aim to eliminate residual tumor cells that have maintained the capacity to reinitiate tumor growth after intensive conventional therapy. Preclinical models that more closely mimic in vivo tumor growth than standard monolayer cultures are needed. Sphere formation under anchorage-independent, serum-free conditions has been proposed to enrich for cells with tumor-initiating, stem cell-like properties in various solid cancers. In the present study, we assessed the pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Ewing sarcoma cell lines A673, TC-32, and TC-71 were originally received from the cell line bank at Children’s Hospital Los Angeles; CADO-ES1 from DSMZ (Braunschweig, Germany); and VH-64 from F van Valen (Institute of Experimental Musculoskeletal Medicine, University Hospital Münster). The low-passage cell culture DC-ES-6 was established in our laboratory and previously described [ 22 ]. LAN-5 neuroblastoma cells were originally provided by R Seeger (Los Angeles, CA) and HL-60 acute myeloid leukemia cells were purchased from ATCC (Manassas, VA).…”
Section: Methodsmentioning
confidence: 99%
“…Ewing sarcoma cell lines A673, TC-32, and TC-71 were originally received from the cell line bank at Children’s Hospital Los Angeles; CADO-ES1 from DSMZ (Braunschweig, Germany); and VH-64 from F van Valen (Institute of Experimental Musculoskeletal Medicine, University Hospital Münster). The low-passage cell culture DC-ES-6 was established in our laboratory and previously described [ 22 ]. LAN-5 neuroblastoma cells were originally provided by R Seeger (Los Angeles, CA) and HL-60 acute myeloid leukemia cells were purchased from ATCC (Manassas, VA).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, only partial overlap was observed among CD57 high and CD133 + populations of cells, suggesting that CD57 identify different population of Ewing's sarcoma cells with CSC phenotype. Previously, Leuchte et al ( 34 ) argued against a role of CD133 and CD57 as markers of CSCs in Ewing's sarcoma.…”
Section: Ewing's Sarcomamentioning
confidence: 99%
“…Next we sought to test the effects of combined PI3Kα and mTOR inhibition on stem-like cancer cells grown in 3-D. Ewing sarcoma spheroids may not represent a reliable system to study stem-like cancer cell biology 42 . By contrast, we and others have shown that medulloblastoma cells grown under cancer stem cell conditions form 3-D neurospheres that adopt cancer stem cell characteristics 26,4345 .…”
Section: Resultsmentioning
confidence: 99%